2017
DOI: 10.1149/2.1611706jes
|View full text |Cite
|
Sign up to set email alerts
|

Easy Preparation of Electrode Surfaces with Dispersed Size-Controlled Au Nanoparticles by Electrodeposited PPI-Dendrimers as Templates

Abstract: The main target of this work is the preparation of nanostructurated surfaces with size-controlled gold nanoparticles to obtain effective electrocatalytic surfaces. In this paper, we show that dispersed Au nanoparticles (AuNPs) having diameters of less than 3 nm can be synthesized in situ with aminoferrocenyl-and amidoferrocenyl-poly(propyleneimine) (PPI) dendrimers previously electrodeposited onto electrode surfaces. Dendrimers of first, third and fifth generation have been studied and good dispersed non aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 59 publications
(92 reference statements)
0
12
0
Order By: Relevance
“…The complete AFM study, including depth, arithmetic mean roughness (Ra), square average roughness (Rms) and density as a function of the dendrimer deposited mass and relative electrode sur-face area was reported earlier. 12 In short, it was demonstrated that the compactness, as an apparent density calculated from the dendrimer coverage and the AFM depth measurements, slightly increases for the AMN films as the dendrimer generation increases (0.0027, 0.0064 and 0.0132 mg cm −3 for AMN1, AMN3 and AMN5 respectively). The formation of AuNPs causes a drastic increase in the compactness of films (0.024, 0.035 and 0.059 mg cm −3 for Au-AMN1, Au-AMN3 and Au-AMN5 respectively), more pronounced for the fifth generation, as can be seen in Fig.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The complete AFM study, including depth, arithmetic mean roughness (Ra), square average roughness (Rms) and density as a function of the dendrimer deposited mass and relative electrode sur-face area was reported earlier. 12 In short, it was demonstrated that the compactness, as an apparent density calculated from the dendrimer coverage and the AFM depth measurements, slightly increases for the AMN films as the dendrimer generation increases (0.0027, 0.0064 and 0.0132 mg cm −3 for AMN1, AMN3 and AMN5 respectively). The formation of AuNPs causes a drastic increase in the compactness of films (0.024, 0.035 and 0.059 mg cm −3 for Au-AMN1, Au-AMN3 and Au-AMN5 respectively), more pronounced for the fifth generation, as can be seen in Fig.…”
Section: Resultsmentioning
confidence: 96%
“…The morphology of these electrode surfaces, with and without AuNPs, was studied earlier. 12 Briefly, the dependence of the sizes of obtained holes and the porosity and density of AMN films on the dendrimer generation, allowed us to prepare monodispersed inter-or intra-dendrimer AuNPs with generation-dependent sizes. The tapping mode AFM imaging (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The is 2.0 × 10 −8 A/m 2 , and is 8.0 × 10 −7 A/m 2 , based on literature and measurement ( SI Appendix , Fig. S5 ) ( 69 , 70 ).…”
Section: Methodsmentioning
confidence: 99%